Expression of lymphoid structure-associated cytokine/chemokine gene transcripts in tumor and protein in serum are prognostic of melanoma patient outcomes - Karapetyan, Lilit; AbuShukair, Hassan M.; Li, Aofei; Knight, Andrew; Al Bzour, Ayah Nedal; MacFawn, Ian P.; Thompson, Zachary J.; Chen, Ann; Yang, Xi; Dadey, Rebekah; Karunamurthy, Arivarasan; De Stefano, Danielle Vargas; et al. (Frontiers in Immunology, 2023)
Background: Proinflammatory chemokines/cytokines support development and maturation of tertiary lymphoid structures (TLS) within the tumor immune microenvironment (TIME). In the current study, we sought to investigate the prognostic value of TLS-associated chemokines/cytokines (TLS-kines) expression levels in melanoma patients (PTs) by performing serum protein and tissue transcriptomic analyses, and to then correlate these data with PT tumor clinicopathological and TIME characteristics. Methods: Levels of TLS-kines in PT sera were quantitated using a custom Luminex Multiplex Assay. The Cancer Genomic Atlas melanoma cohort (TCGA-SKCM) and a Moffitt Melanoma cohort were used for tissue transcriptomic analyses. Associations between target analytes and survival outcomes, clinicopathological variables, and correlations between TLS-kines were statistically analyzed. Results: Serum of 95 PTs with MEL were evaluated; 48 (50%) female, median age of 63, IQR 51-70 years. Serum levels of APRIL/TNFSF13 were positively correlated with levels of both CXCL10 and CXCL13. In multivariate analyses, high levels of serum APRIL/TNFSF13 were associated with improved event-free survival after adjusting for age and stage (HR = 0.64, 95% CI 0.43-0.95; p = 0.03). High expression of APRIL/TNFSF13 transcripts was significantly associated with improved OS in TCGA-SKCM (HR = 0.69, 95% CI 0.52-0.93; p = 0.01) and in Moffitt Melanoma PTs (HR = 0.51, 95% CI: 0.32-0.82; p = 0.006). Further incorporation of CXCL13 and CXCL10 transcript levels in a 3-gene index revealed that high APRIL/CXCL10/CXCL13 expression was associated with improved OS in the TCGA SKCM cohort (HR = 0.42, 95% CI 0.19-0.94; p = 0.035). Melanoma differentially expressed genes positively associated with high APRIL/CXCL10/CXCL13 expression were linked to tumor infiltration by a diverse array of proinflammatory immune cell types. Conclusion: Serum protein and tumor transcript levels of APRIL/TNFSF13 are associated with improved survival outcomes. PTs exhibiting high coordinate expression of APRIL/CXCL10/CXCL13 transcripts in their tumors and/or elevated levels of the 3 TLS-kines in their sera displayed superior OS. Further investigation of TLS-kine expression profiles related to clinical outcomes in larger cohort studies is warranted.